The Study of Quantum Relativity: Teleportation and the Story of Transferring the Throne of Queen Balqis - Nurul Faridah; Bambang Supriadi; Maryani Maryani (Studies in Philosophy of Science and Education, 2022)
The modern science that we have and learn today is written in the Qur’an. The Qur'an has shown humans about its comprehensive and global miracles because the Qur'an remains in accordance with the latest developments that humans have achieved until today. This study aims to examine the quantum theory of annihilation in the story of teleportation and transfer of the throne of queen balqis. This study uses a descriptive qualitative research method in a literature study by analyzing related books and journals. The results show that the teleportation and displacement of the Queen Balqis Throne can be approached by explaining the quantum theory of Annihilation. The quantum theory of Annihilation relates to Teleportation and the transfer of the throne of Queen Balqis, but many questions still arise. That is, the quantum theory of Annihilation is not sufficient to explain the transfer of the throne of Queen Balqis. However, in terms of data suitability, the quantum annihilation theory is appropriate and rational with moving the throne of Queen Balqis.